THE STRUCTURE OF SEA CUCUMBER COMMUNITY OF HOLOTHUROIDE CLASS OF THE SUGI ISLAND WATERS NIUR PERMAI VILLAGE MORO DISTRICT KARIMUN REGENCY - Alviana, Nur; Zulkifli, Zulkifli; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Sea cucumbers from the Holothuroidea class are spineless and soft-bodied animals like cucumbers. This research was conducted in March 2021 in Niur Permai Village, Moro District, Karimun Regency, Riau Islands Province. This study aims to determine the structure of the sea cucumber community in the waters of Sugi Island, Niur Permai Village. The method used in this research is the survey method. Sampling was done purposive sampling, by determining 3 (three) stations. The results of the research on sea cucumber community structure in the waters of Sugi Island, Niur Permai Village found 4 (four) species, and the most common family found was from Stichopodidae including Stichopus horrens, S.hermanni, S.ocellatus. Based on the calculation of the highest abundance value found at station III, namely 900 ind/ha found in coral and seagrass areas, while the lowest abundance value at station II, namely 7.66 ind/ha found in muddy sand areas. Diversity index values (H') ranged from 1.37-1.94 with a uniformity index (E) ranging from 0.69-0.97 and a dominance index (C) ranging from 0.27-0.29. The overall distribution pattern of sea cucumber class Holothuridea is clustered. Based on the analysis of sediment organic matter in the waters of Sugi Island, Niur Permai Village, the highest average value is 2.85% and the lowest percentage is 2.08%. The results of the analysis of the sediment fraction at each station are gravel sand. Water quality parameters measured in the research location have good environmental conditions for sea cucumber life.